Fungitoxicity Against Botrytis Cinerea of a Flavonoid Isolated from Pseudognaphalium Robustum - Cotoras-Tadic, M; Aguirre-Quintana, M; Aguirre-Quintana, M; Mendoza-Espinola, L; Mendoza-Espinola, L; Castro-Valenzuela, P; Castro-Valenzuela, P (2011)
The fungotoxicity against Botrytis cinerea of a flavonoid isolated from Pseudognaphalium robustum was analyzed. Two absorption column chromatographies and one semipreparative thin layer chromatography were used to purify the active flavonoid. It was determined, by 1H-NMR spectroscopy and co-elution with standards in HPLC, that this compound was 5,7-dihydroxy-3,8- dimethoxyflavone (gnaphaliin A). To determine the fungitoxicity of the purified compound, the effect on in vitro mycelial growth and conidial germination was studied. The compound concentration that reduced mycelial growth by 50% was 45.5 ?g/mL. This compound also partially affected conidial germination of B. cinerea, reduced oxygen consumption by germinating conidia and affected the integrity of plasma membrane. Finally, using cyclic voltammetry, it was shown that the purified flavone had a pro-oxidant effect. © 2011 by the authors.